Type D Personality and Essential Hypertension in Semarang City, Indonesia: A Primary Healthcare Center-based Case-Control Study (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Type D personality is defined as the interaction between negative affectivity (NA) and social inhibition (SI). Hypertension has the highest cases in primary healthcare center (PHC) in Semarang City compared to other non-communicable diseases. This study aims to determine type D personality role on essential hypertension. It was a case-control study conducted at the PHC in Semarang City from January 2020 to March 2021 with 139 cases and 139 controls among 18-60 years old patients. Sample collection was performed by stratified random sampling. The instruments used were the DS-14 scale, structured questionnaire IPAQ-SF, food frequency questionnaire, and the Holmes and Rahe Stress Scale, while data were analyzed using logistic regression. The prevalence of type D personality in the case group (64%; 95%CI: 55.9%-72.1%) was higher than in the control (36.7%; 95%CI: 28.7%-44.7%). Type D personality was discovered to be significantly associated with essential hypertension (OR: 3.07; 95%CI: 1.83-5.16). After other covariates adjustment, the association was still statistically significant (AdjOR: 2.41; 95%CI: 1.32-4.41).